Algal pigments distribution and phytoplankton group assemblages in the coastaltransitional environment - Boka Kotorska Bay (southeastern Adriatic Sea) - Krivokapić, Slađana; Bosak, Sunčica; Viličić, Damir; Kušpilić, Grozdan; Drakulović, Dragana; Pestorić, Branka (2018)
Phytoplankton assemblages and pigment distribution were determined in the transitional Boka Kotorska Bay. Samples were collected four times from three stations in the inner part of the Bay between April 2008 and March 2009. Microscopic analysis revealed that the phytoplankton was composed of marine diatoms, dinoflagellates, cryptophytes, chlorophytes and coccolithophorids. Aside from fucoxanthin as the dominant biomarker pigment, alloxanthin, 19′-hexanoyloxyfucoxanthin, peridinin and chlorophyll b provided indicative contributions. Fucoxanthin and alloxanthin showed significant correlation with the phytoplankton chlorophyll a biomass throughout the investigated period. In November 2008, the diatoms were outcompeted by coccolithophorids, which probably efficiently absorbed nutrients during a period of their reduced supply. Due to the reduced nutrient input, in the summer, the phytoplankton community in the Bay was composed mostly of marine dinoflagellates, cryptophytes, and chlorophytes.
Prisutnost zajednica fitoplanktona i rasprostranjenost pigmenata utvrđivani su u tranzicijskim vodama Bokokotorskog zaljeva. Uzorci su prikupljeni četiri puta na tri lokaliteta u unutrašnjosti Zaljeva u periodu između travnja 2008. i ožujka 2009. godine. Mikroskopskom analizom utvrđeno je da fitoplankton čine morske dijatomeje, dinoflagelati, kriptofiti, klorofiti i kokolitoforidi. Pored fukoksantina kao dominantnog biomarkerskog pigmenta, bili su zastupljeni i aloksantin, 19′-heksanoiloksifukoksantin, peridinin i klorofil b‏. Fukoksantin i aloksantin su pokazali značajnu korelaciju sa klorofilom a kao indikatorom biomase fitoplanktona tijekom čitavog perioda ispitivanja. U studenom 2008. godine, dijatomeje su nadjačale kokolitoforide, koji su vjerovatno efikasno apsorbirali nutrijente tijekom perioda u kojem je njihova dostupnost bila smanjena. Kao rezultat smanjenog unosa nutrijenata, u ljetnom periodu, zajednicu fitoplanktona u Bokokotorskom zaljevu sačinjavali su uglavnom morski dinoflagelati, kriptofiti i klorofiti.
Bibliografija: str. 46-49.
Summary ; Sažetak.
Keywords: Fitoplanktonske zajednice -- Alge -- Algalni pigment -- Raspodjela pigmenta; Bokokotorski zaljev -- Jadransko more